Digital Learning Strategies for Enhancing Islamic Religious Education in the Era of Artificial Intelligence - Khairul Amin; Junaidi; Lia Amelia; Evi Yuslinar; Bambang Wahyu Susanto (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the potential of Artificial Intelligence (AI) and digital learning strategies in enhancing Islamic Religious Education (IRE) in the digital age. Using a qualitative approach and a systematic literature review (SLR) methodology, this research examines various AI-powered tools and their integration into Islamic education. The study identifies key benefits such as personalized learning experiences, real-time assessments and feedback, and interactive learning tools that can enhance student engagement and understanding of Islamic teachings. AI-driven platforms, including adaptive learning systems, chatbots, and gamification, were found to provide tailored content and foster an engaging learning environment for diverse learners. However, challenges such as the digital literacy gap among educators and the need for AI tools to align with Islamic values were also highlighted. The study concludes that AI can support teachers in delivering more personalized instruction and expand access to Islamic education, but successful implementation requires overcoming these challenges. Recommendations for future research include exploring the effectiveness of AI in specific Islamic education settings, adapting AI tools to diverse cultural contexts, and investigating the long-term impact of AI on student outcomes in IRE.